Optimizing the tractive performance of 4WD tractors operating on a frictional soil. - Al-Hashem, Hasan Ahmed A. (Cranfield University, 1996)
The present investigation aimed to develop a simple method of predicting the optimum performance of a medium size 4WD tractor performing a draught operation on a frictional soil in particular. The data obtained could provide an appropriate ballasting recommendation for the optimum combination of tractor power, weight and working speed on such soils taking account of minimizing the undesirable effect of soil compaction. A wheel torque/weight transducer system was developed to measure the forces applied on the tractor wheels. One side of a MF 3065 tractor was equipped and instrumented. The system fitted to each wheel consists of three link transducers, two modified wheel discs, wheel angular position measuring device and fifth wheel device together with a Datalogger and a portable computer. All transducers output were linear with a coefficient of determination, R² > 0.9994 and were repeatable. Field experiments were conducted on sandy loam soil condition to determine the peak tractive efficiency of the tractor in work. Three operating variables at three levels were considered including tractor ballast weight, working speed and implement pull setting. Soil compaction effect for a particular traction situation was assessed by three field measurement methods of soil dry density, penetration resistance and water infiltration rate. Five relationships of predicting tractor ballast recommendation proposed by Reece (1968), Brixius and Zoz (1976), Dwyer (1978), Gee-Clough et al. (1982) and Bloom et al. (1983) were chosen to present the existing ballast method. These relationships were modified to be at similar conditions of wheel slip, coefficient of traction and tractor power to describe the ballast recommendation as a non- dimensional number Rn and takes the form of: W/P* = Rn/V where W is the dynamic tractor weight, P* is the tractor axle power and V is the actual forward speed. The results of the study were compared with two concepts of existing work. Firstly, with the average ballast recommendation value used for all types of soil. The comparison showed that the ballast recommendation in terms of weight-power ratio is expected to be approximately 70 % of the amount of ballast recommended by the existing work for frictional-cohesive soil at a given speed operating at similar conditions of wheel slip and coefficient of traction. This means for the same pull at a particular power less weight is required because the soil under consideration has high angle of internal shearing resistance, φ than the average soil type. The ballast recommendation for a medium size 4WD tractor operating on a frictional soil (sandy loam) with optimum slip value of 10 % is determined as : W/P* = 1.3/V compared with the value suggested by the theory for all soil types which is generally accepted as : W/P* = 1.9/V when operating under similar conditions of 10 % wheel slip and 0.4 coefficient of traction. Secondly, the results were compared with an empirical approach of Dwyer et al. (1974), Gee-Clough et al. (1978) with the aim to extract the most related data to the tyre tractive performance operating on a sandy loam soil from all other types of soil. There was found to be a reasonable agreement between the two data sets which gave confidence to the accuracy of the modified equation to predict the ballast required when operating at maximum tractor efficiency. The recommended equation for relating maximum coefficient of traction (Ct)max and mobility number M for the frictional soil (sandy loam) becomes : (Cͭͭͭͭͭᵗ)max = 0.62- 0.82/M for rear wheel (Cᵗ)max = 0.42 - 0.52 /M for front wheel The measured tractor thrust force was also compared with the calculated using the classical theory of traction mechanics (Janosi and Hanamoto, 1961 and Reece, 1967) and the results showed no significant difference between the measured and calculated thrust values at 95% confidence level. The three methods of soil compaction measurement showed that there is a direct relationship between the tractor weight and /or wheel slip, and soil compaction effect. However, infiltration rate method seems to be the most sensitive one to demonstrate the compaction damage to the soil. The results obtained from this measurement indicated that under the optimum power conditions the tractor caused an acceptable level of soil compaction compared to the most serious effect that can occur. The optimum conditions in this soil type involved operating at 10 % wheel slip with mobility number of 6.5.
Keywords: 4WD tractor; draught; ballasting; transducer; traction; soil